Reallocation of time spent on sedentary behavior by time spent on physical activity reduces dynapenia in older adults: a prospective cohort study - Silva, Rizia Rocha; Galvão, Lucas Lima; Martins, Giovana Silva; Meneguci, Joilson; Virtuoso Júnior, Jair Sindra; Santos, Douglas de Assis Teles; Tribess, Sheilla (São Paulo Medical Journal, 2023)
BACKGROUND: Dynapenia is characterized by mobility limitations in the older population when combined with aggravating behavioral factors that can increase the risk of morbidity and mortality. OBJECTIVE: To investigate the hypothetical effects of reallocation of time spent on sedentary behavior (SB), moderate-to-vigorous physical activity (MVPA), and sleep on dynapenia in older adults. DESIGN AND SETTING: A prospective cohort study using exploratory surveys in Alcobaça City, Bahia State, Brazil. METHODS: In total, 176 older adults (≥ 60 years) of both sexes participated in this study. Dynapenia was assessed using the handgrip strength test with cutoff points of < 27 kg for men and < 16 kg for women. MVPA and SB were assessed using the International Physical Activity Questionnaire, and sleep was assessed using the Pittsburgh Sleep Quality Index. RESULTS: Effects on reallocation were found for the shortest times, such as 10 minutes (odds ratio (OR) 0.92; 95% confidence interval (CI): 0.85–0.99); substituting MVPA with SB increased the chances of dynapenia by 58.0% (95% CI: 1.01–2.49). Analyzing the substitution of 60 minutes/day of SB with 60 minutes/day of MVPA revealed a protective effect, with a lower OR for dynapenia of 37.0% (OR 0.63; 95% CI: 0.40–0.99). The reallocation of sleep time did not significantly reduce dynapenia. CONCLUSIONS: Substituting the time spent sitting with the same amount of time spent on MVPA can reduce dynapenia, and a longer reallocation time confers greater health benefits in older adults.